Effects of Partial Supporting Pile Removal from Deep Foundation Pits by Shallow Excavation Method in Loess Areas. (29th August 2021) - Zheng, Yunxin; Hu, Zhiping; Ren, Xiang; Wang, Rui; Zhang, Enxiang; Long, Zhao
Abstract : Partial supporting piles removal from deep foundation pit may lead to large-scale foundation pit collapse, resulting in severe consequences. Various studies have investigated the underpinning technology of cutting abutment piles by combining field monitoring and numerical simulation, but there are few studies on cutting supporting piles of foundation pit by the shallow excavation method. Taking an actual deep and large foundation pit as an example, the finite element method (FEM) was adopted to study the surface settlement and the changing trend of the force and displacement of the supporting pile caused by cutting piles during the shallow excavation of double tunnels. The FEM results were verified with the field monitoring data. The simulation results show that the surface settlement around the foundation pit mainly occurs at the pile cutting stage under different excavation sequences (0D, 1D, 2D), and the main distribution area is the one-fold diameter area outside the double tunnel. After the supporting piles are partially cut, the bending moment and displacement of the lower part of the broken piles differ significantly due to different excavation sequences, but the bending moment and displacement of the upper part of the broken piles are basically similar. In the process of removing the supporting piles, the Earth pressure behind the piles is redistributed, and the load is mainly transferred to the adjacent supporting piles outside the tunnel within the radius of one time of the tunnel diameter. However, the load is not evenly transferred to the adjacent supporting piles. Some recommendations for the reinforcement scheme of the supporting structure during cutting supporting piles in deep foundation pit are also proposed. The research results can provide theoretical basis and practical guidance for the construction of similar projects in the future.